Analisis Penerapan PSAK 5 (Revisi 2009) terhadap Pengungkapan Segmen Operasi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) - Pardede, Robert Pius; Ernawati, Tri (Institut Bisnis dan Informatika Kesatuan, 2017)
The International Accounting Standards Board (IASB) is committed to improve their standards’ quality, which is the global accounting standards that reflect information in financial statements as transparent and comparable for public purposes. The International Accounting Standards (IAS) and the International Financial Reporting Standards (IFRS) provide guidelines in creating and interpreting companies’ financial statements (Iatridis & Dalla, 2011). The purpose of this research was to assess the impact of the application of PSAK 5 (revised 2009). PSAK 5 (revised 2009) requires segment disclosure based on the internal reporting reviewed by the operation decision maker. PSAK 5 (revised 2000) requires companies to disclose segments information based on the format of the primary and secondary segments as identified per products / services that generate the same level of risk and return. The six analytical frameworks developed for this research, namely: (1) analysis of the presentation of segment information based on PSAK 5 (revised 2000) versus PSAK 5 (revised 2009), (2) analysis of the determination and identification of operational decision-making, (3) the analysis of the definition and identification operating segments between industry sectors, (4) analysis of segment aggregation, (5) analysis of determination of the reportable segments, and (6) analysis of reported segment disclosures. In conclusion, generally, the disclosure of segment information based on PSAK 5 (revised 2009) by using the management approach yields a more complete segment report, by conveying more relevant segmental information from the standpoint of management's internal performance than the previous standard, which was PSAK 5 (revised 2000). This research found significant changes related to an increase in the disclosure of segment disclosure in business segments, segment aggregation, and basic information on company's segmental performance measurement in Indonesia.